2017
DOI: 10.3390/ijms18071449
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Histone Acetyltransferase GCN5 or PCAF Knockdown on Urothelial Carcinoma Cells

Abstract: Disturbances in histone acetyltransferases (HATs) are common in cancers. In urothelial carcinoma (UC), p300 and CBP are often mutated, whereas the GNAT family HATs GCN5 and PCAF (General Control Nonderepressible 5, p300/CBP-Associated Factor) are often upregulated. Here, we explored the effects of specific siRNA-mediated knockdown of GCN5, PCAF or both in four UC cell lines (UCCs). Expression of various HATs and marker proteins was measured by qRT-PCR and western blot. Cellular effects of knockdowns were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…6 , B and C ), suggesting that the acetylation of Lys-90 by GCN5 has a biological function different from that of Lys-31 by PCAF, which is involved in the defense responses of the host. Similar opposing effects of acetylation by PCAF and GCN5 were reported in tumor cells ( 33 , 34 ). Acetylation on different lysine residues in the tumor repressor p53 caused a tumor-promoting role of GCN5 and a tumor-repressing role of PCAF ( 33 ).…”
Section: Discussionsupporting
confidence: 77%
“…6 , B and C ), suggesting that the acetylation of Lys-90 by GCN5 has a biological function different from that of Lys-31 by PCAF, which is involved in the defense responses of the host. Similar opposing effects of acetylation by PCAF and GCN5 were reported in tumor cells ( 33 , 34 ). Acetylation on different lysine residues in the tumor repressor p53 caused a tumor-promoting role of GCN5 and a tumor-repressing role of PCAF ( 33 ).…”
Section: Discussionsupporting
confidence: 77%
“…A series of bladder cancer cell lines, representing different stages and grades of the disease, were used as described previously ( Koutsogiannouli et al, 2017 ). Most of the functional experiments were conducted using the moderately differentiated cell line BFTC905, which was established from a grade 2 stage C urothelial carcinoma ( Cheng et al, 1995 ).…”
Section: Methodsmentioning
confidence: 99%
“…PCAF is an important member of the GCN5-related N-terminal acetyltransferase family, which has histone acetyltransferase activity and plays an important role in regulating various cellular physiological activities including cell growth, differentiation, apoptosis, and so on [30,31]. Jia et al found that PCAF is downregulated in hepatocellular carcinoma (HCC) tissues, and overexpression of PCAF in HCC cells can promote autophagy and cause tumor cell death [9].…”
Section: Discussionmentioning
confidence: 99%